STRATEGI PENGEMBANGAN INDUSTRI KREATIF UNTUK INOVASI - Hesty Heryani; Agung Cahyo Legowo; Indra Prapto Nugroho (Department of Agroindustrial Technology, Bogor Agricultural University, 2020)
Changes are very fast and full of uncertainty, such as the current condition of COVID-19, which makes it very difficult for supply chain managers even though they already have a very good regularity. Changes in consumer preferences are very fast and even difficult to predict. The purpose of research and development was to identify the factors that influence the performance and competitiveness of the creative industry for innovation. It needed to be informed that the development strategy was not only providing information, availability of goods, money, and innovation, but there were pluses in terms of developing knowledge, knowing the strength map, implementing efficiency accompanied by value. Analysis of Strengths, Weaknesses, Opportunities, and Threats (SWOT) was used in determining alternative strategies, while the analysis focus strategy used the Quantitative Strategic Planning Matrix (QSPM) method by considering the Total Attractiveness Scores obtained. For this reason, the potential and challenges in a series of processes (transformation activities and transaction activities) of a product must be carefully scrutinized, so that added value can be created at each stage. The results of the SWOT analysis resulted in five alternative strategies, which were then followed by a QSPM analysis to obtain the total attractiveness scores. The results of the analysis gave the highest total value on the importance of potential resource availability with a value of 15.862 followed by the second to fifth order, the need to understand rapid market changes (14.840), build partnerships (14.646), standardized and sustainable products (14.123) and develop efficiency principles for competitiveness (12.288), respectively. Recommendations are given that resource potential and rapid response to market demands in addition to the other three factors should be considered in the development strategy for innovation in creative industries. Keyword: COVID-19, innovation, SWOT, QSPM, total attractiveness scores